Chance Debugged - Dohrn, Daniel (Lato Sensu: Revue de la Société de philosophie des sciences, 2021)
A ‘Big Bad Bug’ threatens Lewis’s Humean metaphysics of chance (Lewis 1986a, p. XIV); his Principal Principle provides an intuitive link between chance and credence. Yet on the one hand, certain future developments are incompatible with the true theory of chance, but on the other hand, such future developments have a positive chance to occur. The combination of these two claims with the Principal Principle leads to inconsistent credences. I present a Humean solution to the Bug: chances are relative to a limited perspective. The perspective comprises facts available as evidence to an ideal cognizer at a point in space-time. As a consequence, the same future event can have different chances of occurring provided the perspective is different. I show how this dissolves the Bug.